Using the Theory of Motivated Information Management to Understand Direct Information Seeking on COVID-19 from Close Contacts - Tengku Mohd Azzman Shariffadeen, Tengku Siti Aisha; A. Manaf, Aini Maznina; Syed Zainudin, Sharifah Sofiah (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: As the COVID-19 pandemic spread like wildfire in 2020, initially, little was known about the pandemic. Various parties including local governments, health agencies, medical researchers, and frontliners made concerted efforts to ensure the accuracy, timeliness, and reliability of the information released to the public. Accordingly, a major focus of this study is to examine the factors influencing COVID-19 direction information seeking from close contacts as determined by the theory of motivated information management (TMIM). MATERIALS AND METHODS: A cross-sectional survey using Google form was distributed to undergraduate students pursuing communication courses at public universities in Malaysia. RESULTS: Out of six hypotheses, only two are not supported. Consistent with TMIM, outcome expectancy and target efficacy predict direct information seeking on COVID-19 from close contacts. Further, target efficacy mediates the relationship between outcome expectancy and direct information seeking. CONCLUSION: Overall, the study found empirical support for TMIM as a useful framework for understanding COVID-19 information management. The repercussions of these findings on TMIM as well as key factors that may influence decision-making on information seeking during a global health pandemic are also discussed.